Cockney Dialect and Slang in Selected British Films and TV Series - Vtípilová, Aneta (Univerzita Pardubice, 2017)
This thesis is devoted to the lexico-semantic features of Cockney dialect and slang in selected British films and TV series. The theoretical part focuses on the description of Cockney dialect and slang in general and it thoroughly describes three main lexico-semantic features of Cockney, namely general vocabulary of Cockney slang, rhyming slang and back slang. The analytical part studies the meanings, usage and connotations of the aforementioned features in regard to the situational context of the films and TV series.
Cockney dialekt a slang ve vybraných britských filmech a seriálech
Keywords: Cockney; dialekt; slang; rýmovaný slang; význam; konotace; Cockney; dialect; slang; rhyming slang; meaning; connotation